Microbial quality of mung bean (Vigna Radiata, L. Wilczek) sprouts from selected wet markets of Manila City, Philippines - Villaflor, Edwin James Bacalangco; Gabriel, Alonzo Alulod (2006)
ABSTRACT This study was done to determine the microbial quality of mung bean sprouts vended in selected wet markets in the city of Manila Philippines. Documentations of sprout production, handling, transportation and vending practices of sprout vendors and producers were done. The microbial quality parameters included (TPC), yeast and mold counts (YMC), lactic acid bacteria (LAB) counts, total coliform (TCC) and generic E. coli counts (GEC). Five wet markets were randomly chosen as sample representatives for the City of Manila, two of which are Class A markets (average monthly income of 60,000 pesos or more) and the rest are Class B markets (average income of 30,000 pesos or more). Two sprout producers were observed for their sprout production practices. Face-to-face interviews conducted with the vendors showed that most vendors did not observe proper hygiene and acceptable vending practices. Sprout producers have likewise unacceptable production practices. Results showed that mung bean sprouts from the different testing sites had TPCs in the range of 5.46-7.20 log10 cfu/g, YMCs of 4.84-5.71 log10 cfu/g, LAB counts of 5.00-6.14 log10 cfu/g, TCCs of 4.70-7.13 log10 cfu/g and GEC of <4.00-4.48 log10 cfu/g. The relatively large microbial populations observed may be attributed to the unacceptable mung bean sprout production and vending practices.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mung bean -- Microbiology